1993
DOI: 10.1126/science.8342022
|View full text |Cite
|
Sign up to set email alerts
|

Greater Susceptibility to Mutations in Lagging Strand of DNA Replication in Escherichia coli than in Leading Strand

Abstract: Models of DNA replication in Escherichia coli involve an asymmetric DNA polymerase complex that replicates concurrently the leading and the lagging strands of double-stranded DNA. The effect of asymmetry on mutagenesis was tested with pairs of plasmids containing the unidirectional ColE1 origin of replication and a single lesion located in the leading or lagging strand. The lesion used was the covalent adduct that the chemical carcinogen N-2-acetylaminofluorene (AAF) forms with the C-8 position of guanine. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 15 publications
2
76
1
Order By: Relevance
“…Many authors have found that error rates are higher on the lagging strand (e.g. Trinh and Sinden 1991;BasicZaninovic et al 1992;Veaute and Fuchs 1993;Roberts et al 1994;Iwaki et al 1996;Thomas et al 1996). However, Fijałkowska et al (1998), measuring the mutation rate in the lactose operon incorporated into the Escherichia coli chromosome in two opposite directions, have found that mutation rate in the gene inserted in the direction of the leading strand is higher.…”
Section: Chargaff Rules [A] ‫ס‬ [T] and [G] ‫ס‬ [C]mentioning
confidence: 99%
“…Many authors have found that error rates are higher on the lagging strand (e.g. Trinh and Sinden 1991;BasicZaninovic et al 1992;Veaute and Fuchs 1993;Roberts et al 1994;Iwaki et al 1996;Thomas et al 1996). However, Fijałkowska et al (1998), measuring the mutation rate in the lactose operon incorporated into the Escherichia coli chromosome in two opposite directions, have found that mutation rate in the gene inserted in the direction of the leading strand is higher.…”
Section: Chargaff Rules [A] ‫ס‬ [T] and [G] ‫ס‬ [C]mentioning
confidence: 99%
“…In addition, in E. coli, it has been observed that the manner in which a given DNA lesion is dealt with depends on the direction of replication [20]. When a plasmid containing a defined DNA lesion was transformed into E. coli cells, the resulting mutation frequency was distinctly different depending on whether the lesion was located on the leading-strand template versus the lagging-strand template [20].…”
Section: Introductionmentioning
confidence: 99%
“…The question of differential replication fidelity within the two strands is a subject of current interest (21)(22)(23)(24)(25)(26)(27). A strand preference of the SOS process, if observed, would be of mechanistic importance.…”
mentioning
confidence: 99%